ANALISA STAKEHOLDER DALAM KEBIJAKAN PEMBANGUNAN DI INDONESIA - Prakoso, Gilang Reno; Munandar, Adis Imam (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
Today the world's need for infrastructure continues to increase in line with increasing eco-nomic activity. Infrastructure is one of the determinants of the smoothness and acceleration of development. The availability of adequate infrastructure facilities will stimulate development in a region or country. In Indonesia, infrastructure development is a major challenge that must be overcome immediately. The lack of quality of Indonesia's infrastructure is inseparable from funding problems. The government has identified that the provision of infrastructure through the Public Private Partnership (PPP) scheme is an alternative for infrastructure financing that involves the role of business entities. And it cannot be denied that development, especially infrastructure, is closely related to national resilience as is the determination of the Indonesian people to realize the national goals contained in the Preamble to the 1945 Constitution. Keywords: Development, infrastructure, KPBUJEL Classification: O10, O18, O20